Eccentricity index as an adjunctive indicator of coronary ischemia: Correlation with ischemic burden based on myocardial perfusion imaging - Pratama, Prima; Christina, Edelyn; Soeriadi, Rd; Kartamihardja , Achmad (Deka in Medicine, 2025)
BACKGROUND: One of the main challenges in managing CAD is the measurement of ischemic burden experienced by patients, which can influence therapy decisions and prognosis. The Left Ventricular Eccentricity Index (EI) has become a potential additional indicator for assessing the severity of ischemia in CAD patients. OBJECTIVES: This study aims to analyze the correlation between the Left Ventricular EI and ischemic burden measured using myocardial perfusion imaging (MPI) in CAD patients. METHODS: This retrospective cohort study was conducted at Dr. Hasan Sadikin Hospital in Bandung from August 2023 to June 2024. Data were collected using MPI with 99mTc sestamibi gated SPECT. Statistical analysis was performed using the Mann-Whitney U test and Spearman's correlation. RESULTS: A total of 78 patients who met the inclusion and exclusion criteria were included in this study. The analysis showed that EI values in both the stress and rest phases were significantly higher in the group with ischemic burden ≥10%. The median ejection fraction value in the stress phase was also lower in this group (p = 0.013). Correlation analysis revealed a significant relationship between EI and ischemic burden (p < 0.05). CONCLUSION: This study demonstrates that EI can be used as an additional indicator to assess the severity of ischemia in CAD patients. Integrating EI into routine MPI protocols can improve the accuracy of risk stratification and management of CAD patients.